2022
DOI: 10.3390/ijms231911196
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Severity of Early Chronic Kidney Disease on Oxidative Stress in Patients with and without Type 2 Diabetes Mellitus

Abstract: Early Chronic Kidney Disease (CKD) is a condition that tends to progress to End-Stage Kidney Disease (ESKD). Early diagnosis of kidney disease in the early stages can reduce complications. Alterations in renal function represent a complication of diabetes mellitus (DM). The mechanisms underlying the progression of CKD in diabetes could be associated with oxidative and inflammatory processes. This study aimed to evaluate the state of inflammation and oxidative stress (OS) on the progression of CKD in the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…One of the biochemical pathways of cellular damage that induce high glucose levels is cellular oxidative stress, a mechanism recognized in almost all tissues of the organism in uncontrolled diabetes mellitus. Oxidative stress was shown to induce glomerular inflammation, which increases glomerular volume; moreover, oxidative stress leads to glomerular function failures, especially an increase in urinary protein excretion and a decrease in glomerular filtration fraction [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the biochemical pathways of cellular damage that induce high glucose levels is cellular oxidative stress, a mechanism recognized in almost all tissues of the organism in uncontrolled diabetes mellitus. Oxidative stress was shown to induce glomerular inflammation, which increases glomerular volume; moreover, oxidative stress leads to glomerular function failures, especially an increase in urinary protein excretion and a decrease in glomerular filtration fraction [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in the pro-inflammatory cytokines IL-6 and TNF-α was observed in the T2DM group. The authors concluded that in the patients with type 2 DM, oxidative imbalance was characterized by an increase in oxidative markers and a decrease in antioxidant defenses (SOD, TAC, and GPx) [7].…”
mentioning
confidence: 99%